Friend or Foe? Cooperation and Learning in High-Stakes Games - Oberholzer-Gee, Felix; Waldfogel, Joel; White, Matthew W (The Review of Economics and Statistics, 2010)
Why do people frequently cooperate in defiance of their immediate incentives? One explanation is that individuals are conditionally cooperative. As an explanation of behavior in one-shot settings, such preferences require individuals to be able to discern their opponents' preferences. Using data from a television game show, we provide evidence about how individuals implement conditionally cooperative preferences. We show that contestants forgo large sums of money to be cooperative; they cooperate at heightened levels when their opponents are predictably cooperative; and they fare worse when their observable characteristics predict less cooperation because opponents avoid cooperating with them.